2019
DOI: 10.3390/s19092062
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Micro-Battery for Powering Smart Contact Lens

Abstract: In this paper, we demonstrate the first attempt of encapsulating a flexible micro battery into a contact lens to implement an eye-tracker. The paper discusses how to scale the battery to power various circuits embedded in the contact lens, such as ASIC, photodiodes, etc., as well as how to combine the battery with external harvested energy sources. The fabricated ring battery has a surface area of 0.75 cm2 yielding an areal capacity of 43 µAh·cm−2 at 20C. Based on simulated 0.35-µm CMOS ASIC power consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…To ensure uninterrupted operation, energy supply to the electronic contact lens needs careful consideration. For example, Nasreldin et al have investigated the use of flexible batteries that are integrated on the lenses . However, battery lifetime and replacement become an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure uninterrupted operation, energy supply to the electronic contact lens needs careful consideration. For example, Nasreldin et al have investigated the use of flexible batteries that are integrated on the lenses . However, battery lifetime and replacement become an issue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antenna design in electronic contact lenses is very important. Previous designs that relied on a serpentine structure for power transfer and communications might impede eyesight, since the eyeball's physical structure is not carefully considered. Therefore, our design was based on a spiral coil antenna, which was fabricated on a polyimide flexible substrate and encapsulated with polydimethylsiloxane (PDMS) .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated that electrodeposition can be used to prepare NiCo 2 O 4 /graphene [13], while Chen et al prepared graphene hybrid nanosheet arrays via a one-pot procedure [14]; these synthesized graphene electrodes delivered good electrochemical performances. More recently, rapid research progress has been made in exploring flexible anode materials delivering high storage capacity and remarkable long-term cyclability [15][16][17]. As an allotrope of carbon, CNT electrodes offer several outstanding properties, such as excellent flexibility, fast charge transport, large surface-to-volume ratio, good chemical stability, high electrical conductivity and high reversible capacity [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility of the substrates is one of the major breakthroughs in the design of new generation sensor systems and other electronic devices [11][12][13][14][15]. Due to this reason, in our following studies, we obtained gas sensors using flexible Kapton HN®polyimide films (from DuPont™).…”
Section: Substrate Materialsmentioning
confidence: 99%